2016
DOI: 10.1016/j.actamat.2016.08.072
|View full text |Cite
|
Sign up to set email alerts
|

The effect of interstitial carbon on the mechanical properties and dislocation substructure evolution in Fe40.4Ni11.3Mn34.8Al7.5Cr6 high entropy alloys

Abstract: A systematic study of the effects of up to 1.1 at. % carbon on the mechanical properties and evolution of the dislocation substructure in a series of a high entropy alloys (HEA) based on Fe 40.4 Ni 11.3 Mn 34.8 Al 7.5 Cr 6 is presented. Transmission electron microscopy (TEM), synchrotron X-ray diffraction (XRD) and atom probe tomography (APT) were used to show that all the alloys are single-phase f.c.c. random solid solutions. The lattice constant, determined from synchrotron XRD measurements, increases linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
106
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 434 publications
(120 citation statements)
references
References 57 publications
8
106
0
Order By: Relevance
“…However, such twinning is difficult to achieve at room temperature because the resolved shear stress is insufficient to reach the critical stress for twinning2021. Another issue is the relatively low yield strength (0.2–0.6 GPa) caused by the fcc structural characteristics of the alloy1420222324. Here, we effectively induce twinning in an HEA at room temperature and exploit the induced twinning to improve the cryogenic tensile properties, particularly the yield strength, of the material.…”
mentioning
confidence: 99%
“…However, such twinning is difficult to achieve at room temperature because the resolved shear stress is insufficient to reach the critical stress for twinning2021. Another issue is the relatively low yield strength (0.2–0.6 GPa) caused by the fcc structural characteristics of the alloy1420222324. Here, we effectively induce twinning in an HEA at room temperature and exploit the induced twinning to improve the cryogenic tensile properties, particularly the yield strength, of the material.…”
mentioning
confidence: 99%
“…This is because the interstitial atom can produce a lattice asymmetric distortion, and the substitutional solute is spherically symmetric in crystal lattice distortions. However, most studies have found that brittle boride precipitation is unavoidable by arc melting preparation, and it is difficult to obtain high boron solubility in the boron-containing HEAs [1][2][3]. The results of this paper prove that laser rapid solidification can play an effective role in preventing the precipitation of the boride phase in HEA coatings.…”
Section: Discussionmentioning
confidence: 56%
“…Nevertheless, previous studies utilized an arc melting technique to prepare bulk alloy, and reported that the complex brittle boride precipitation is inevitable after solidification in the HEAs, due to high thermodynamic enthalpy of the boride compound [1,6,7]. In comparison to the dominant arc melting synthesis technique, the laser cladding technique-which has a rapid solidification rate of 10 3 -10 6 • C/s-has a greater ability to prepare high performance HEA coatings in engineering applications [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] It has been reported that HEAs exhibit many attractive properties, such as good ductility, high hardness, strong oxidation resistance, wonderful corrosion resistance, superior resistance to temper softening, super wear resistance, strong fatigue, and fracture resistance. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] These remarkable properties make HEAs suitable advanced structural materials for many industries, including aerospace and ocean engineering.…”
mentioning
confidence: 99%